2021
DOI: 10.1016/j.envres.2020.110405
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 pandemic in the lens of food safety and security

Abstract: The recently emerged coronavirus disease (COVID-19), which has been characterised as a pandemic by the World Health Organization (WHO), is impacting all parts of human society including agriculture, manufacturing, and tertiary sectors involving all service provision industries. This paper aims to give an overview of potential host reservoirs that could cause pandemic outbreak caused by zoonotic transmission. Amongst all, continues surveillance in slaughterhouse for possible pathogens transmission is needed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 83 publications
(44 reference statements)
0
75
0
4
Order By: Relevance
“…Seventeen studies were collected under the AGRI2 category (Alekseev, Ruschickaya, & Yurchenko, 2020; Barcaccia et al, 2020; Blay‐Palmer et al, 2020; Christiaensen et al, 2020; Deaton & Deaton, 2020; Dupouy & Gurinovic, 2020; Fanzo et al, 2020; Gregorioa & Ancog, 2020; Hossain, 2020; Kennedy, Jafari, Stamoulis, & Callens, 2020; Ma, Peng, Soon, et al, 2020; Mausch et al, 2020; Popovic et al, 2020; Rowan & Galanakis, 2020; Savary et al, 2020; Singh et al, 2020; Sperling et al, 2020).…”
Section: Analysis and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies were collected under the AGRI2 category (Alekseev, Ruschickaya, & Yurchenko, 2020; Barcaccia et al, 2020; Blay‐Palmer et al, 2020; Christiaensen et al, 2020; Deaton & Deaton, 2020; Dupouy & Gurinovic, 2020; Fanzo et al, 2020; Gregorioa & Ancog, 2020; Hossain, 2020; Kennedy, Jafari, Stamoulis, & Callens, 2020; Ma, Peng, Soon, et al, 2020; Mausch et al, 2020; Popovic et al, 2020; Rowan & Galanakis, 2020; Savary et al, 2020; Singh et al, 2020; Sperling et al, 2020).…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…The export ban caused a reduction in world GDP to 13% in the first half of 2020, which suggests that the global food supply is affected by the exchange rate (Ma et al, 2020). The World Bank has stated that COVID‐19 pandemic disrupts the domestic supply chain while the global supply chain remains unaffected (Ibidem).…”
Section: Analysis and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meat processing sector, as well as the entire food industry, needs to prepare for epidemics and pandemics with new technological solutions, including a greater degree of automation and robotics, to reduce human food contact and the human density in workplaces to minimize food waste and ensure food safety [ 71 ].…”
Section: Proposed Preventive Measures In Slaughterhouses During Thmentioning
confidence: 99%
“…Notwithstanding, according to several international organizations, the risk of infection through consumption of contaminated foods is being considered to be very low ( Government of Canada, 2020 ; CDC, 2020b ; EC, 2020 ; FDA, 2020 ). However, SARS-CoV-2 pandemic has had a great impact in the food industry, as well as in the food safety due to the high economic losses ( Ma et al, 2020 ; Mardones et al, 2020 ). For example, recently White et al (2021) have reported that seafood catches, imports and exports in the US seafood sector have declined by 40%, 37% and 43%, respectively, when compared to the previous year.…”
Section: Persistence and Stability Of Sars-cov-2 In Foodsmentioning
confidence: 99%